x*x-18x+81=4+81

Simple and best practice solution for x*x-18x+81=4+81 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*x-18x+81=4+81 equation:


Simplifying
x * x + -18x + 81 = 4 + 81

Multiply x * x
x2 + -18x + 81 = 4 + 81

Reorder the terms:
81 + -18x + x2 = 4 + 81

Combine like terms: 4 + 81 = 85
81 + -18x + x2 = 85

Solving
81 + -18x + x2 = 85

Solving for variable 'x'.

Reorder the terms:
81 + -85 + -18x + x2 = 85 + -85

Combine like terms: 81 + -85 = -4
-4 + -18x + x2 = 85 + -85

Combine like terms: 85 + -85 = 0
-4 + -18x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '4' to each side of the equation.
-4 + -18x + 4 + x2 = 0 + 4

Reorder the terms:
-4 + 4 + -18x + x2 = 0 + 4

Combine like terms: -4 + 4 = 0
0 + -18x + x2 = 0 + 4
-18x + x2 = 0 + 4

Combine like terms: 0 + 4 = 4
-18x + x2 = 4

The x term is -18x.  Take half its coefficient (-9).
Square it (81) and add it to both sides.

Add '81' to each side of the equation.
-18x + 81 + x2 = 4 + 81

Reorder the terms:
81 + -18x + x2 = 4 + 81

Combine like terms: 4 + 81 = 85
81 + -18x + x2 = 85

Factor a perfect square on the left side:
(x + -9)(x + -9) = 85

Calculate the square root of the right side: 9.219544457

Break this problem into two subproblems by setting 
(x + -9) equal to 9.219544457 and -9.219544457.

Subproblem 1

x + -9 = 9.219544457 Simplifying x + -9 = 9.219544457 Reorder the terms: -9 + x = 9.219544457 Solving -9 + x = 9.219544457 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = 9.219544457 + 9 Combine like terms: -9 + 9 = 0 0 + x = 9.219544457 + 9 x = 9.219544457 + 9 Combine like terms: 9.219544457 + 9 = 18.219544457 x = 18.219544457 Simplifying x = 18.219544457

Subproblem 2

x + -9 = -9.219544457 Simplifying x + -9 = -9.219544457 Reorder the terms: -9 + x = -9.219544457 Solving -9 + x = -9.219544457 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + x = -9.219544457 + 9 Combine like terms: -9 + 9 = 0 0 + x = -9.219544457 + 9 x = -9.219544457 + 9 Combine like terms: -9.219544457 + 9 = -0.219544457 x = -0.219544457 Simplifying x = -0.219544457

Solution

The solution to the problem is based on the solutions from the subproblems. x = {18.219544457, -0.219544457}

See similar equations:

| -14=-(-2+2) | | -x*x+x+.25=1.25 | | 2m+6=2(2m+3)-2 | | -x*-x+x+.25=1.25 | | 3(c-8)+13=5c+5 | | -4.4=2x+25.6 | | 4.2z=-4(0.6-1.2) | | 2mx^2-mx+1=0 | | 3(6-x)-8=2 | | 5x+6x-64=3x-65 | | 4v-2=10 | | 5x^2=2x+1 | | 6x+19x=25 | | 4x+2+6x-1=13x+1 | | 18-6y=0 | | 4x+3=42 | | 10=3f+1 | | 2b+1=7 | | 4x-5=-1x-30 | | -2x-10+7x=6x+14-4x | | x+14=-32-9 | | -6y+13=-5(y-4) | | 13x=-7-3-20 | | 4x+3x=-35 | | Y+13-7y=-5(y-4) | | 16x+2=-17 | | 22-5x+9x=-2(-6x+5) | | 3y^2+z= | | -33-6y+19=-23y+56+7y | | 7(x+2)=5x+2+6x | | 3x^3-10x^2+50x= | | -2a-9= |

Equations solver categories